Exploring perspectives on ChatGPT integration in education: A student-centered study of benefits, concerns, and global implications for responsible AI integration - Lawrence Ibeh; Noah Cheruiyot Mutai; Olufunke Mercy Popoola; Nguyen Manh Cuong; Sandra Ejiofor (Research in Learning Technology)
For this study, 350 university students in Germany were surveyed to understand how they perceive ChatGPT’s educational advantages and challenges. Using a combination of quantitative and qualitative methods, it found out that students tend to see ChatGPT as helpful for academic performance (53.14%), writing (47.14%), and exam preparation (50.00%). Nonetheless, a large majority of people expressed doubt regarding its ability to understand queries (61.72%), reliability (52.29%), privacy (52.57%), bias (47.43%), security (55.14%) and displaced jobs (56.29%). These concerns were reinforced by open ended responses, which showed that attitudes towards AI can be based on factors such as a person’s digital literacy and their experience with AI. In the study, the researchers propose a need to incorporate AI education into curricula in order to teach students to critically assess AI- generated content and to identify biases. Moreover, it suggests setting ethical standards that AI systems need to meet such as accuracy, security, and transparency. Perspectives between cultures vary, and require the teacher to conduct more global research, and approach teaching context specifically. The overarching goal is to promote the thoughtful, ethical, and context-aware integration of AI into educational practices worldwide.